Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 5)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 5)" [g0973005.jpg], n.d.